Exploring pedagogical and ethical dimensions of AI use in EFL classrooms: teachers’ views from private high schools - Akyıldız, Seçil Tümen (Gürhan DURAK, 2025)
This study examines EFL teachers' perceptions regarding the pedagogical benefits, ethical dilemmas, and institutional challenges associated with the implementation of AI tools in language classes. The research was conducted at private high schools in a small city, Türkiye, employing a qualitative design within a constructivist framework. Ten teachers were selected through purposive sampling to ensure a diverse array of experiences and expertise with AI tools. Subsequently, they were interviewed using a semi-structured format. Reflexive thematic analysis identified three primary themes: perceived instructional advantages, ethical concerns, and institutional limits. Although educators commended AI for its capacity to assist in lesson design, foster student autonomy, and enhance engagement, they also voiced concerns around data privacy, academic integrity, and students' excessive reliance on AI. Inadequate policies, lack of managerial support, and insufficient professional development opportunities were institutional challenges that hindered the successful utilization of AI. The findings indicate that educators necessitate clear regulations from their institutions, continuous professional support, and ethical frameworks to utilize AI tools responsibly in language instruction.
Keywords: Instructional Technologies; Öğretim Teknolojileri